Low altitude unmanned aerial vehicle for characterising remediation effectiveness following the FDNPP accident. (January 2016) - Martin, P.G.; Payton, O.D.; Fardoulis, J.S.; Richards, D.A.; Yamashiki, Y.; Scott, T.B.
Abstract: On the 12th of March 2011, The Great Tōhoku Earthquake occurred 70 km off the eastern coast of Japan, generating a large 14 m high tsunami. The ensuing catalogue of events over the succeeding 12 d resulted in the release of considerable quantities of radioactive material into the environment. Important to the large-scale remediation of the affected areas is the accurate and high spatial resolution characterisation of contamination, including the verification of decontaminated areas. To enable this, a low altitude unmanned aerial vehicle equipped with a lightweight gamma-spectrometer and height normalisation system was used to produce sub-meter resolution maps of contamination. This system provided a valuable method to examine both contaminated and remediated areas rapidly, whilst greatly reducing the dose received by the operator, typically in localities formerly inaccessible to ground-based survey methods. The characterisation of three sites within Fukushima Prefecture is presented; one remediated (and a site of much previous attention), one un-remediated and a third having been subjected to an alternative method to reduce emitted radiation dose. Highlights: Contamination near FDNPP was mapped with a UAV. Effectiveness of remediation is observed. Sub-meter resolution mapping is achieved. Isotopic nature of radiation is determined.